2011
DOI: 10.1074/mcp.o111.009381
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Evaluation and Minimization of Nonenzymatic Deamidation in Proteomic Sample Preparation

Abstract: Identification of deamidated sites in proteins is commonly used for assignment of N-glycosylation sites. It is also important for assessing the role of deamidation in vivo. However, nonenzymatic deamidation occurs easily in peptides under conditions commonly used in treatment with trypsin and PNGase F. The impact on proteomic sample preparation has not yet been evaluated systematically. In addition, the 13 C peaks of amidated peptides can be misassigned as monoisotopic peaks of the corresponding deamidated one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
188
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(198 citation statements)
references
References 29 publications
6
188
2
2
Order By: Relevance
“…To further confirm the quality of the identification, a manual check for the spectrum of each glycopeptide was performed. Sometimes database searches return some false-positive identifications of deamidated peptides because the 13 C peaks of amidated peptides can be wrongly assigned as the monoisotopic peaks of the corresponding deamidated peptides (56). The close N or Q to the motif of glycosylation can also cause false-positive identification if the evidence is not enough to confirm which one is really deamidated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the quality of the identification, a manual check for the spectrum of each glycopeptide was performed. Sometimes database searches return some false-positive identifications of deamidated peptides because the 13 C peaks of amidated peptides can be wrongly assigned as the monoisotopic peaks of the corresponding deamidated peptides (56). The close N or Q to the motif of glycosylation can also cause false-positive identification if the evidence is not enough to confirm which one is really deamidated.…”
Section: Methodsmentioning
confidence: 99%
“…Nonenzymatic deamidation occurs in peptides under basic conditions commonly used in treatment with trypsin and PNGase F. Our previously published results showed that digesting peptides in pH 6.0 and releasing glycans in pH 5.0 significantly reduced the artifacts of glycosite identification from deamidated peptides introduced in sample preparation (56). Solutions with pH 6.0 and with pH 5.0 were used to extract A431 proteins and remove glycans of peptides after enrichment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Nonenzymatic deamidation has previously been observed during the extended incubations with either trypsin or PNGase F digestions (35). We have previously demonstrated that false positive glycosylations may occur in large-scale datasets by mis-annotation of chemically deamidated Asn residues within an N-linked sequon (21,22).…”
Section: Identification and Quantification Of Phosphopeptides And Formentioning
confidence: 99%
“…This gives rise to an approximate 1.2% glycosite FDR (39/3246) (supplemental Table S6). A further improvement to these negative control experiments could include the combination of an optimized trypsin and PNGase F protocol described in (35) with or without incubation of the tryptic peptides at increased pH and temperature to observe the formation of deamdiated peptides.…”
Section: Identification and Quantification Of Phosphopeptides And Formentioning
confidence: 99%
“…The rates are significantly higher at alkaline pH, which is typical (for instance) in trypsin digestion. Thus, it is difficult to distinguish a natural protein deamidation, which could be a marker of a disease or protein ageing, from artifactual deamidation during proteomic sample preparation [201,202]. Deamidation proceeds via formation of a cyclic intermediate by condensation of the side-chain amide group with the carbonyl group of the following amino acid, and subsequent opening of this ring upon hydrolysis with water.…”
Section: Protein Deamidationmentioning
confidence: 99%